Clinical Buddhist Chaplaincy Spiritual Care in the US Catholic Healthcare System - Zhen, Guan (Journal of International Buddhist Studies, 2024)
This study utilized an actual participant qualitative field research paradigm to collect data for examining and analyzing the work of a clinical Buddhist chaplain within a rural, Catholic medical center in the US. Quantitative data collected from patient visits (n=1,329; total visits (tv.)=1,443) provided information for measuring the spiritual care needs of patients and the efficiency and consistency of a clinical Buddhist chaplain’s work. The results demonstrate that prayers and pastoral counseling for Catholic and Protestant patients (n=1,265; 95.17%) comprised the dominant work content of a clinical Buddhist chaplain. This study suggests that traditional Christian chaplaincy is practiced even by Buddhist chaplains in a rural, religious medical institution.